Developing Animation Video-based Demonstration Experiments in Teaching Solubility and Solubility Product Materials - Marlina Marlina; Riyanto Riyanto (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
Education in the 21st century is learning to prepare a generation that prioritizes advances in information and communication technology (ICT) as a medium for students to develop products in the form of animated videos, demonstrations and experiments. This study aims to produce valid, interesting, and effective learning media. This research is an ADDIE development research with five stages: analysis, design, development, implementation, and evaluation. The subjects in this study were three high school students with 60 students and three teachers and two validators—data collection instruments in questionnaires and tests. The data analysis technique in this research and development is a descriptive statistical analysis technique of percentages to process data from the validator's assessment, student responses and test results. Qualitative descriptive describes data in the form of suggestions and comments from the validator. The animation video media validation results obtained an average score of material expert validation, and media expert validation obtained a percentage of 84%, classified as very good. The results of the student response questionnaire to the learning media obtained a percentage of 86% with an exciting category. Finally, the test results obtained 100% results with effective criteria where all students met the minimum standard of completeness set by the school, namely 76 for chemistry subjects.